'We're like a gang, we stick together': experiences of ventricular assist device communities. (1st June 2018) - Standing, Holly C; Exley, Catherine; MacGowan, Guy A; Rapley, Tim
Abstract: Background: Ventricular assist devices (VADs) are a relatively new development in the management of advanced heart failure. In the UK, VAD recipients comprise a unique group of less than 200 patients. This is the first paper to explore the experience of VAD communities, the extent to which communities are developed around the device, and how these influence the experience of living with the VAD. Methods: Qualitative interviews were conducted with 20 VAD recipients (implanted as a bridge to transplantation), 11 interviews also included the VAD recipients' partners. Interpretive phenomenology was employed as the theoretical basis guiding the analysis of the interviews. Results: Four key themes emerged from the data: the existence of VAD communities; experiential knowledge and understanding; social comparisons; and the impacts of deaths within the VAD community. Many of the interviewees valued the VAD communities and the relationships they had formed with fellow recipients. The beneficial impacts of the VAD communities included offering recently implanted patients a realistic view of what to expect from life with a VAD; this could aid them in accepting and adapting to the changes imparted by the device. However, negative impacts of the VAD communities were also reported, in particular following deaths within the group, which were a source of distress for many of the interviewees. Conclusions: In general, the VAD communities appeared to be a beneficial source of support for the majority of interviewees. Consideration should be given to how these communities could be supported by clinicians.